(untitled) - Yaron, Bruno (New York, 1996)
This book is delicated to understanding the processes governing the fate of pollutants, originating from both agriculture and industry, in soils. Investigated here are the properties of the interacting materials, pollutant partitioning between the soil phases, pollutant behaviour in soils affected by environmental factors
Suy thoái và bảo tồn môi trường đất,Bạc màu đất và bảo tồn tài nguyên đất đai
Keywords: soil pollution,zone of aeration